A implementação da política nacional de resíduos sólidos na gestão municipal de Santarém - Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
This study aims to identify the performance of municipal management in the application of the National Policy of Solid Waste in Santarém. The methodology used was the bibliographic and documentary research in legislation and historical data of the National Sanitation Information System, with historical cut from 2010 to 2019 of solid waste collection in Santarém. There was an increase in the population in the municipality, which is in line with the increasingly frequent number of solid waste, generating more than 40 thousand tons of solid waste in 9 years. Currently, the majority of the population has waste collections 2-3 times per week in each neighborhood, increasing the number of neighborhoods served. With the expansion of the collection service, there was also an increase in the amounts spent for this purpose, as observed throughout the study, with an expense of R $ 9 million in 2017. As for the management of these wastes, there was greater spending in 2014, reaching the figure of R $ -17,757,618.36. In assessing this per capita expenditure, it is observed that the cost is R $ 83.44 per inhabitant in 2014. Thus, it can be observed that the average unit cost of the household and public waste collection service in Santarém per ton had the highest increase in 2014, reaching the amount of R $ 155.84 per ton. In 2017, the amount of mass collected from household and public waste was 1.06 kg per inhabitant, daily. It is noteworthy that the Municipality of Santarém already has municipal municipal waste management legislation as recommended by PNRS, but there are still difficulties that hinder the application of this set of laws, such as the lack of financial resources, requiring the support of the Federal Government and State to effect the integrated and sustainable management of municipal waste. It was concluded that the main approach in waste management is to raise awareness of generating sources, that is, society in general, which consumes in excess, and wastes a lot of raw materials, risking the lack of them in the very near future.
Keywords: Política Nacional de Resíduos Sólidos; Coleta; Resíduos; Gestão Pública; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS